Prediction of the n-hexane/water and 1-octanol/water partition coefficients for environmentally relevant compounds using molecular simulation - Nuno M. Garrido (2012)
In recent years molecular simulation has emerged as a useful tool to predict physical properties of complex chemical systems. A methodology to estimate the n-hexane/water and 1-octanol/water partition coefficients of environmentally relevant solutes, namely substituted alkyl-aromatic molecules, chlorobenzenes, polychlorinated biphenyls (PCBs) and polychlorinated diphenyl ethers (PCDEs) using molecular simulation is elucidated here. The partition coefficients are calculated based on the absolute solvation Gibbs energies in each phase which are estimated from molecular dynamics simulations employing the thermodynamic integration approach. Very encouraging results, with average absolute deviations of 0.4 log P units are presented. Consequently, this molecular-based approach with a strong physical background can provide reliable prediction of the partition coefficients in different solvent pairs without the a priori knowledge of experimental data. (C) 2011 American Institute of Chemical Engineers AIChE J, 58: 19291938, 2012